Comprehensive Analysis of Artery Ligation Intervention in Placenta Percreta Management: A Systematic Review - Nurseta, Tatit; Leksono, Setio (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: The artery ligation technique has been adopted as a life-saving strategy to minimize bleeding in obstetrical and pelvic procedures. However, there are only a few studies on the use of arterial ligation in surgeries for abnormally invasive placentation (AIP). The purpose of this systematic study is to assess how well arterial ligation in managing blood loss during placenta percreta surgery and assess the associated complications and adverse events. Material and Methods: Systematic Reviews and Meta-Analyses Preferred Reporting Items (PRISMA) framework was used in this study. Studies on arterial ligation techniques in placenta percreta surgery were included based on criteria focusing on estimated blood loss, operative time, and adverse events. A comprehensive literature search across multiple databases was performed, resulting in three studies that met the inclusion criteria. Results: The three studies included in the review with a total of 193 patients. The findings show that IIAL significantly decreased the projected amount of blood loss compared to control groups. In one study, bilateral IIAL showed lower blood loss (1076 ± 545 ml) compared to other interventions, while another study demonstrated that IIAL resulted in lower estimated blood loss compared to control groups. However, hypogastric artery ligation (HAL) was associated with higher blood loss in one study. Despite its effectiveness in controlling blood loss, complications such as common iliac artery thrombosis, pseudoaneurysms, and limb ischemia were reported, though with low incidence. Conclusion: Arterial ligation, particularly IIAL, could be a viable strategy for managing blood loss during placenta percreta surgery.